СТАНОВЛЕНИЕ И РАЗВИТИЕ ТЕМЫ СЕМЬИ В ХУДОЖЕСТВЕННОЙ ЛИТЕРАТУРЕ (Scientific journal of the Fergana State University, 2025)
In this article, the Genesis, evolutionary evolution of the topic of the family in Uzbek literature, the oldest written monuments of the image of the family, the Qur'an and Hadith, the reflection of folk oral creativity in the current literary process, are subjected to analysis with examples. In the coverage of the research topic, methods of psychological, comparative-typological, structural, hermeneutic analysis were used.